Clinical Application of Liquid Biopsy in Non-Hodgkin Lymphoma - Lv, Liwei; Liu, Yuanbo (Frontiers in Oncology, 2021)
Non-Hodgkin lymphoma (NHL) is a common type of hematological malignant tumor, composed of multiple subtypes that originate from B lymphocytes, T lymphocytes, and natural killer cells. A diagnosis of NHL depends on the results of a pathology examination, which requires an invasive tissue biopsy. However, due to their invasive nature, tissue biopsies have many limitations in clinical applications, especially in terms of evaluating the therapeutic response and monitoring tumor progression. To overcome these limitations of traditional tissue biopsies, a technique known as “liquid biopsies” (LBs) was proposed. LBs refer to noninvasive examinations that can provide biological tumor data for analysis. Many studies have shown that LBs can be broadly applied to the diagnosis, treatment, prognosis, and monitoring of NHL. This article will briefly review various LB methods that aim to improve NHL management, including the evaluation of cell-free DNA, circulating tumor DNA, microRNA, and tumor-derived exosomes extracted from peripheral blood in NHL.